ChemInform Abstract: Organocatalytic Oxidation of Secondary Alcohols Using 1, 2‐Di(1‐naphthyl)‐1, 2‐ethanediamine (NEDA). Issue 11 (March 2015) - Al‐Hunaiti, Afnan; Raeisaenen, Minna; Pihko, Petri; Leskelae, Markku; Repo, Timo
Abstract Secondary alcohols, even sterically hindered ones, are selectively oxidized by using tert‐butyl hydroperoxide as an oxidant and 1, 2‐di(1‐naphthyl)‐1, 2‐ethylenediamine as catalyst.